ACQUIRED VITELLIFORM DETACHMENT IN MULTIPLE MYELOMA. Issue Volume 11:Issues 1(2017:Winter) (2017) - El Ameen, Alaa; Mrejen-Uretsky, Sarah; Abraham, Julie; Souied, Eric H.; Cohen, Salomon Y.
Abstract : Purpose: To report a case of subfoveal acquired vitelliform detachment in a patient with multiple myeloma. Methods: Case report. Results: A 65-year-old man was referred for treatment of a serous macular detachment considered to be caused from chronic central serous chorioretinopathy or adult pseudovitelliform macular dystrophy. His medical history revealed an untreated multiple myeloma. Systemic chemotherapy was undertaken and resulted in a rapid resolution of the detachment. Conclusion: Multiple myeloma may be considered as a possible cause of vitelliform macular detachment. Abstract : A vitellifrorm macular detachment, considered to be secondary to central serous chorioretinoapthy or adult pseudovitelliform macular detachment, was related to multiple myeloma and resolved with systemic chemotherapy.